Mitigation of protein fouling by magnesium ions and the related mechanisms in ultrafiltration process. (January 2023) - Zou, Hui; Huang, Jiahui; Zhang, Meijia; Lin, Hongjun; Teng, Jiaheng; Huang, Zhengyi
Abstract: Although protein is an important membrane foulant in the water body that may be significantly affected by the coexisting common cation magnesium (Mg 2+ ), the effect of Mg 2+ on protein fouling is rarely reported. In this context, this study selected bovine serum albumin (BSA) as the model foulant, and investigated its fouling characteristics at different Mg 2+ concentrations (0–100 mM). Filtration tests showed that the protein fouling can be significantly mitigated by adding Mg 2+, and the specific filtration resistance (SFR) of pure BSA (3.56 × 10 14  m kg −1 ) was at least 5 times that of BSA-Mg 2+ solutions (0.5–100 mM). In addition, an optimal Mg 2+ concentration exists, which can achieve the lowest BSA SFR. A series of characterizations indicated that the main contributors to the differences in BSA SFR were the changes in BSA adhesion capacity and the thickness and structure of the foulant layer. Basically, the above results were attributed to the hydration repulsion effect of Mg 2+, which prevented tight adhesion of foulants to the membrane. Moreover, the lowest BSR SFR at 1 mM Mg 2+ was achieved not only by the hydration repulsion effect but also by the particle size compression due to the conformational change of BSA molecules. This combined effect led to the lowest foulant retention on the membrane surface and delivered to the lowest SFR. This study conducts a thorough inspection into the specific effect of Mg 2+ on protein fouling and provides a fresh insight into protein fouling control in the UF process. Graphical abstract: Image 1 Highlights: Addition of magnesium ions (Mg 2+ ) significantly reduced protein fouling of ultrafiltration. Lowest specific filtration resistance (SFR) of BSA was achieved at Mg 2+ concentration of 1 mM. Protein fouling mitigation was attributed to hydration repulsion effect caused by Mg 2+ . Lowest SFR stemmed from combined effect of hydration repulsion and particle size compression. Darcy's Law and XDLVO theory gave a sound explanation for the protein fouling behaviours.